Modernism and the ideology of history : literature, politics, and the past - Williams, Louise Blakeney (Cambridge University Press, 2002)
Louise Williams explores the cyclical nature of historical memory in the work of five writers: Yeats, Pound, Hulme, Ford and Lawrence. Modernists, Williams argues, changed their attitude to history as a result of important conflicts within the period. This study will be essential reading for anyone interested in modernist writing.